The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41422-020-00445-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific transcriptional imprinting and heterogeneity in human innate lymphoid cells revealed by full-length single-cell RNA-sequencing

Abstract: The impact of the microenvironment on innate lymphoid cell (ILC)-mediated immunity in humans remains largely unknown. Here we used full-length Smart-seq2 single-cell RNA-sequencing to unravel tissue-specific transcriptional profiles and heterogeneity of CD127+ ILCs across four human tissues. Correlation analysis identified gene modules characterizing the migratory properties of tonsil and blood ILCs, and signatures of tissue-residency, activation and modified metabolism in colon and lung ILCs. Trajectory analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(173 citation statements)
references
References 65 publications
6
167
0
Order By: Relevance
“…Further evidence for TCR gene rearrangements in other ILC subsets has recently been demonstrated in human studies through sophisticated single-cell transcriptome analyses that revealed gene expression patterns associated with tissueresidency and migration in human ILCs (66). In this report, blood ILC1s (EOMES -/+ ) are shown to uphold the expression of T-cell related-genes such as CD3, CD4, CD5, CD6, CD27, LEF1.…”
Section: Tcr Gene Rearrangements In Ilcsmentioning
confidence: 63%
See 1 more Smart Citation
“…Further evidence for TCR gene rearrangements in other ILC subsets has recently been demonstrated in human studies through sophisticated single-cell transcriptome analyses that revealed gene expression patterns associated with tissueresidency and migration in human ILCs (66). In this report, blood ILC1s (EOMES -/+ ) are shown to uphold the expression of T-cell related-genes such as CD3, CD4, CD5, CD6, CD27, LEF1.…”
Section: Tcr Gene Rearrangements In Ilcsmentioning
confidence: 63%
“…with CXCR3 + Th1 cells (66). These observations suggest that ILC1s are more akin to CD4 + and CD8 + T cells and that in their lifetime, they have undergone a maturation process in the thymus.…”
Section: Tcr Gene Rearrangements In Ilcsmentioning
confidence: 81%
“…MAIT cells expressed TRAV1, TRAV2 and SLC4A10 . ILC2 expressed PTGDR2, HPGDS, IL1RL1 and KRT1 64 and were found in the fetal samples.…”
Section: Methodsmentioning
confidence: 94%
“…Mouse lung ILC2s are relatively insensitive to IL-25 compared with IL-33 ( 28 ) due to low expression of the receptor ( 29 ). Although tissue-specific receptor expression and cytokine sensitivity in human ILC2s are not fully established ( 14 , 30 , 31 ), such data would inform cytokine candidacy for induction of EGPA in patients and reveal patient-specific correlations between individual tissue cytokine changes and specific organ involvement.…”
Section: Discussionmentioning
confidence: 99%